(untitled) (Journal of the College of Basic Education, 2019)
This research aims at identifying the common patterns at the level of academic achievement for students of the Department of Information and Libraries for the academic years (2006-2007) to (2010-2011), due to the difficulty of getting the graduate students’ grades before this date, as well as the accumulation of the students’ information in 5he last academic year. 5 The research used the analytical method using data mining technique using clustering method using the weka program to help obtain the final results.